Anatomopathological Assessment of the Diaphragm in Formalin-Fixed, Paraffin-Embedded Sections - Nucci, Ricardo Aparecido Baptista; Jacob-Filho, Wilson; Busse, Alexandre Leopold; Maifrino, Laura Beatriz Mesiano; de Souza, Romeu Rodrigues (Journal of Morphological Sciences, 2018)
Introduction The analysis of frozen muscle biopsies has become a routine method in the evaluation of muscle structure in health and disease. However, the technique for frozen muscle specimens is not widely available in countries with limited medical facilities. The present study aimed to elucidate a reproducible formalin-fixed and paraffin-embedded (FFPE) method for this type of analysis in postmortem muscles.Methods Diaphragm muscle was obtained within 1 hour of sudden death. Diaphragm strips were washed in saline solution, fixed in 10% formalin, frozen at 4°C in a refrigerator, and stored for 24 hours. Then, the tissue samples were processed into paraffin-embedded blocks. Transversal sections were cut from each paraffin block and stained with hematoxylin and eosin, Picrosirius red, Verhoeff-Van Gieson, and Congo red for the qualitative analysis.Results Our analysis indicated a well-preserved muscle.Conclusion In summary, we demonstrate a simple technique for a reproducible FFPE method in postmortem muscle tissues.
Keywords: anatomy; muscle; necropsy; pathology